DISPARITAS PUTUSAN TENTANG IZIN POLIGAMI ANALISIS PERBANDINGAN PUTUSAN HORIZONTAL DI PENGADILAN AGAMA BANDUNG - Elfiana Fitri Wardani; Lena Ishelmiany Ziaharah; Riyan Ramdani (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study is motivated by the existence of judicial disparity in polygamy permit cases, particularly in Decision Number 3107/Pdt.G/2025/PA.Badg and Decision Number 3144/Pdt.G/2025/PA.Badg, despite having relatively similar grounds for application. This research aims to analyze the judges’ legal reasoning in both decisions, identify the juridical factors causing the disparity, and examine them from the perspective of Islamic family law and Indonesian positive law. The method used is normative legal research with a qualitative approach he method used is normative legal research with a qualitative approach using the analysis of primary and secondary legal materials. The results show that the disparity is caused by differences in the interpretation of Article 4 paragraph (2) and Article 5 paragraph (1) of Law Number 1 of 1974, differences in the position of the Compilation of Islamic Law in judicial reasoning, and the absence of clear guidelines regarding the recognition of reasons beyond normative provisions. The first decision applies a limitative approach, resulting in the application being declared inadmissible, while the second decision adopts a non-limitative approach by considering public interest (maslahah) and the prevention of adultery, leading to the approval of the application. This disparity reflects the tension between normative and contextual approaches in religious court practices, which ultimately affects legal certainty and consistency in judicial decisions.